(untitled) (Innovative professional education, 2024)
The study is aimed at analyzing the challenges and opportunities associated with digital transformations in modern educational institutions. The problems of uneven access to digital resources, the need to adapt educational programs and prepare teachers for the use of digital technologies are considered. Key aspects of the impact of digital innovations on learning are explored and strategic approaches to the effective implementation of digital tools are highlighted.